Toward a Stable Global Noctuidae (Lepidoptera) Taxonomy. Issue 3 (3rd May 2021) - Keegan, Kevin L; Rota, Jadranka; Zahiri, Reza; Zilli, Alberto; Wahlberg, Niklas; Schmidt, B Christian; Lafontaine, J Donald; Goldstein, Paul Z; Wagner, David L
Abstract: Noctuidae are one of the world's most diverse, ecologically successful, and economically important animal lineages with over 12, 000 species in 1, 150 genera. We inferred a phylogeny using eight protein-coding genes for the global fauna, greatly expanding upon previous attempts to stabilize Noctuidae higher classification by sampling 341 genera (nearly half represented by their type species) representing 70/76 widely recognized family-group taxa: 20/21 subfamilies, 32/35 tribes, and 18/20 subtribes. We evaluated 17 subfamily-level taxa in detail, discussing adult and larval morphology, life histories, and taxonomic implications of our results. We significantly alter concepts of Acontiinae, Condicinae, Eustrotiinae, Metoponiinae, and Stiriinae. Our results supported recognition of two new subfamilies: Cobubathinae Wagner & Keegan, 2021 subf. nov . and Cropiinae Keegan & Wagner, 2021 subf. nov . Other nomenclatural changes we made are as follows. We moved: 'Acontia' viridifera (Hampson, 1910), 'Azenia' virida Barnes and McDunnough, 1916, Aleptinoides, Austrazenia, Chalcoecia, Megalodes, and Trogotorna to Chamaecleini in Acontiinae; Apaustis to, and reinstated Emmelia as a valid genus in Acontiinae; Allophyes and Meganephria to Cuculliinae; 'Plagiomimicus' navia (Harvey, 1875), Airamia, Alvaradoia, Hypoperigea, Neotarache, and Mesotrosta to Condicinae; Axenus, Azenia, Metaponpneumata, Sexserrata, and Tristyla to Metoponiinae; 'Paramiana' canoa (Barnes, 1907) to Noctuinae; Aucha, Cobubatha, and Tripudia to Cobubathinae; Anycteola and Supralathosea to Oncocnemidinae; Cropia to Cropiinae; Desmoloma to Dyopsinae; Eviridemas and Gloanna to Bryophilinae; Fota and Stilbia to Stiriinae; and Copibryophila, Homolagoa, and Tyta to Noctuidae incertae sedis. We conclude with discussion of instances where current understanding of noctuid biogeography and life histories were changed by our results.